Net zero healthcare: a call for clinician action. (20th September 2021) - Sherman, Jodi D; McGain, Forbes; Lem, Melissa; Mortimer, Frances; Jonas, Wayne B; MacNeill, Andrea J
Abstract : Health professionals are well positioned to effect change by reshaping individual practice, influencing healthcare organisations, and setting clinical standards, argue Jodi Sherman and colleagues